2021
DOI: 10.1002/jbt.22765
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active phthalocyanine metal complexes: Preparation, evaluation of α‐glycosidase and anticholinesterase enzyme inhibition activities, and molecular docking studies

Abstract: In this study, preparation, as well as investigation of α-glycosidase and cholinesterase (ChE) enzyme inhibition activities of furan-2-ylmethoxy-substituted compounds 1-7, are reported. Peripherally, tetra-substituted copper and manganese phthalocyanines (5 and 6) were synthesized for the first time. The substitution of furan-2-ylmethoxy groups provides remarkable solubility to the complex and redshift of the phthalocyanines Q-band. Besides, the inhibitory effects of these compounds on acetylcholinesterase (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…[ 43 ] Another study, Güzel et al reported furan‐2‐ylmethoxy‐substituted copper and manganese Pcs on cholinesterases inhibited AChE with 15.91 and 48.04 μM, respectively. [ 32 ] These results showed that our compounds had higher inhibitory effects than non‐peripherally (4‐isopropylbenzyl)oxy‐substituted and furan‐2‐ylmethoxy‐substituted Pcs compounds.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…[ 43 ] Another study, Güzel et al reported furan‐2‐ylmethoxy‐substituted copper and manganese Pcs on cholinesterases inhibited AChE with 15.91 and 48.04 μM, respectively. [ 32 ] These results showed that our compounds had higher inhibitory effects than non‐peripherally (4‐isopropylbenzyl)oxy‐substituted and furan‐2‐ylmethoxy‐substituted Pcs compounds.…”
Section: Resultsmentioning
confidence: 83%
“…[27,28] Recently, there have been many studies on the pharmacological and biological activities of Pcs in the literature, especially cholinesterase inhibitory effects. [29][30][31][32][33][34][35] Günsel et al reported that non-peripheral 2-mercaptoethanesulfonate substituted metal-free, zinc, and gallium Pcs inhibited AChE and BuChE. [29] Arslan et al investigated in vitro cholinesterases inhibitory effects of 1,2,3-triazole substituted metal-free, zinc, cobalt Pcs, and their water-soluble derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 138 having oxy methyl furan group (L60, Table 7 , entry 1) had the worst inhibitory activity (IC 50 = 902.83 μM) comparing with acarbose (IC 50 = 0.38 μM). 106 Moreover, complexes 139 (IC 50 = 7.08 μM, acarbose = 63.03 μM), 107 141 (IC 50 = 22.21 μM, acarbose = 51.45 μM), 108 and 144 (IC 50 = 2.44 μM, acarbose = 22.80 μM), 110 displayed good inhibitory activity. However, it indicated the efficacy of involved ligands in the order of L62 > L64 > L72.…”
Section: Tetravalent Metal Complexes As α-Glucosidase Inhibitorsmentioning
confidence: 96%
“…There are several systems used to impart self-healing ability to materials ( Figure 1 ). These systems can be classified into two main groups: capsule-based healing (bead, fiber, and/or vascular type and mechanochemical), which is autonomous, and healing by the action of nonautonomous external stimuli [ 1 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%